2015
DOI: 10.1021/acs.molpharmaceut.5b00531
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Platinum–Maurocalcine Conjugate Induces Apoptosis of Human Glioblastoma Cells by Acting through the ROS-ERK/AKT-p53 Pathway

Abstract: Glioblastoma multiforme (GBM) is a highly malignant and aggressive primary brain tumor. In spite of an arsenal of therapeutic interventions, the prognosis of glioblastoma remains very poor. Cisplatin-based therapy is one of the most important chemotherapy treatments for GBM, although its efficacy is limited by drug resistance and undesirable side effects. In the present study, we designed a chimera molecule containing the platinum binding moiety MBL-III-7 (1) attached N-terminal to the sequence of d-maurocalci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In this study, we also found that juglone could activate the p38-MAPK pathway via ROS generation, and pretreatment with SB203580 could reverse the ROS-induced effect. Besides p38-MAPK pathway, many other pathways could be activated by ROS, such as ROS-AMPK-mTOR pathway and ROS-ERK/AKT-p53 pathway [27, 28], which need to be validated in gliomas. Juglone could also exert cytotoxic effect as a Pin-1 (Peptidyl-prolyl cis/trans isomerase 1) inhibitor through caspase cascade in nasopharyngeal carcinoma [29], which need further research.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also found that juglone could activate the p38-MAPK pathway via ROS generation, and pretreatment with SB203580 could reverse the ROS-induced effect. Besides p38-MAPK pathway, many other pathways could be activated by ROS, such as ROS-AMPK-mTOR pathway and ROS-ERK/AKT-p53 pathway [27, 28], which need to be validated in gliomas. Juglone could also exert cytotoxic effect as a Pin-1 (Peptidyl-prolyl cis/trans isomerase 1) inhibitor through caspase cascade in nasopharyngeal carcinoma [29], which need further research.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that cisplatin-induced cytotoxicity culminates in the activation of apoptosis in cancer cells [34][35][36] . The activation of apoptosis occurs through a mitochondrial membrane potential change and caspase-3 activation 37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the lethal toxins found in these venoms are, in fact, peptides able to block or modulate ion channels in a myriad of cell surfaces (Pineda et al 2014). Since the role of many different ion channels in cancer pathophysiology has become evident, ion channel toxins from spiders and scorpions have been proposed to be used as anticancer peptides (Bubien et al 2004;Wang and Wang 2016;Nicoletti et al 2017), as molecular probes to elucidate the functional aspects of these channels in cancer progression and migration (Rooj et al 2012;Aissaoui et al 2018) or chemically engineered to be used as tumor imaging agent in both diagnoses and prognoses (Aroui et al 2015;Moore et al 2013;Cohen-Inbar and Zaaroor 2016). New drugs aiming at overcoming resistance through the activation of other mechanisms of cell death, like necroptosis, are currently being investigated.…”
Section: Introductionmentioning
confidence: 99%